(untitled) (Journal of Naval Architecture and Marine Engineering, 2010)
In this present work the effects of temperature dependent viscosity and thermal conductivity on the coupling of conduction and Joule heating with MHD free convection flow along a semi-infinite vertical flat plate have been analyzed. The governing boundary layer equations with associated boundary conditions for this phenomenon are transformed to non-dimensional form using the appropriate variables. By the help of the implicit finite difference method with Keller–box scheme, the resulting non-linear system of partial differential equation is then solved numerically. The purpose of this paper is to study the skin friction coefficient, the surface temperature, the velocity and the temperature profiles over the whole boundary layer for different values of the Prandtl number Pr, the magnetic parameter M, the thermal conductivity variation parameter, the viscosity variation parameter and the Joule heating parameter J. The results indicate that the flow pattern, temperature field and rate of heat transfer are significantly dependent on the above mentioned parameters. The local skin friction co-efficient and the surface temperature profiles for different values of viscosity variation parameter are compared with previously published works and are found to be in good agreement. Keywords: Viscosity; thermal conductivity; Joule heating; MHD; conduction; free convection. DOI: 10.3329/jname.v6i2.4994